MORFOLOGIA E COMPOSIÇÃO DO MATERIAL PARTICULADO ATMOSFÉRICO DA BACIA HIDROGRÁFICA DO RIO DOS SINOS (RS) ANALISADOS POR MICROSCOPIA ELETRÔNICA DE VARREDURA - Alves, Darlan Daniel; Montanari Migliavacca Osório, Daniela; Siqueira Rodrigues, Marco Antônio; Schuck, Sabrina (Geochimica Brasiliensis, 2016)
This work aimed the identification and classification of the main types of particles found in the Particulate Matter (PM) collected in two urban and one semi-urban areas of the lower portion of the watershed of Sinos River, RS, Brazil. The identification and classification were carried out from the morphological analysis of the particles by scanning electron microscopy (SEM). Furthermore, by means of dispersive X-ray spectroscopy (EDS), it was attempted to demonstrate the presence of metal elements in the composition of the particles, especially Ni, Cu, Zn, Ba, Cd and Cr. Samples of PM were collected monthly, for a period of 24 hours, from April 2013 to March 2014, with a Stacked Filter Unit sampler (SFU) in 47 mm diameter polycarbonate filter (Millipore, Isopore Membrane Filter). The classification and identification of the origin of the particles was accomplished by comparison with results previously published for similar works. Analysis of the samples revealed the presence of particles from anthropogenic and natural sources, mainly from the burning of fossil fuels and soil resuspension. Metals Ni, Cu, Zn, Ba, Cd and Cr were identified, showing a higher number of occurrences in urban areas, especially at Point 2 (São Leopoldo), suggesting that at this point, the concentration of metals in the MP may be higher.